Predicting defoliator abundance and defoliation measurements using Landsat‐based condition scores. Issue 4 (25th May 2021) - Pasquarella, Valerie J.; Mickley, James G.; Barker Plotkin, Audrey; MacLean, Richard G.; Anderson, Riley M.; Brown, Leone M.; Wagner, David L.; Singer, Michael S.; Bagchi, Robert
Abstract: Remote sensing imagery can provide critical information on the magnitude and extent of damage caused by forest pests and pathogens. However, monitoring short‐term changes in deciduous forest condition caused by defoliating insects is challenging and requires approaches that directly account for seasonal vegetation dynamics. We implemented a previously published harmonic modeling approach for forest condition monitoring in Google Earth Engine and systematically assessed the relative ability of condition change products generated using various model parameterizations for predicting pest abundances and defoliation during the 2016–2018 gypsy moth ( Lymantria dispar ) outbreak in southern New England. Our comparisons revealed that most models made reasonable predictions of changes in canopy condition and egg and larval abundances of L. dispar, indicating a strong correlation between our harmonic‐based estimates of condition change and defoliator activity. The greatest differences in predictive ability were in the spectral domain, with assessments based on Tasseled Cap Greenness, Simple Ratio, and the Enhanced Vegetation Index ranking among the top models, and the commonly used Normalized Difference Vegetation Index consistently exhibiting poorer performance. We also observed notable differences in the magnitude of scores for different baseline periods. Additionally, we found that Landsat‐based condition scores better explained larval abundance than egg mass counts, which have historically been used as a proxy for later‐season larval abundance, indicating that our remote sensing approach may be more accurate and cost‐effective for generating consistent retrospective assessments of L. dispar population abundance in addition to estimates of canopy damage. These findings provide important linkages between spectral changes detected using a harmonic modeling approach and biophysical aspects of defoliator activity, with potential to extend monitoring and prediction to regional or even continental scales. Abstract : We implemented a previously published harmonic modeling approach for forest condition monitoring in Google Earth Engine, and systematically assessed the relative quality of various model parameterizations using reference datasets representing both pest abundance and damage during the 2016–2018 gypsy moth ( Lymantria dispar ) outbreak in southern New England. Our comparisons revealed that while some parameterizations outperformed others, differences were context dependent and most models made reasonable predictions of changes in canopy condition and egg and larval abundances of L. dispar . Our findings provide important guidance on the future use of harmonic modeling approaches for forest condition monitoring and directly advance our ability to quantify spatial and temporal dynamics of defoliator outbreaks at regional or even continental scales.